Discipline -Based Character Education Management: A Case Study in Sindangwangi 02 Elementary School (Educational Management, 2021)
Character education aims to improve the quality of implementation and educational outcomes that lead to the achievement of character building and noble ethics of students in an integrated and balanced manner in accordance with graduation competency standards. This study aims to analyze (1) planning (2) Implementation (3) Evaluation. This research is a qualitative descriptive research. The data collection in this study was carried out directly by the researcher through observation, interviews, and documentation review. Data analysis of the results of this study was carried out based on the interactive analysis model, Miles Huberman. Discipline-Based Character Education Management at Sindangwangi 02 elementary school. The results of the research and data analysis that the author did regarding the management of character education based on discipline, it can be concluded that the implementation of character education at Sindangwangi 02 elementary school is carried out in an integrated manner in every school activity through planning, implementation, and Evaluation. In planning for character education, Sindangwangi 02 elementary school takes steps to determine the vision, mission and goals, values of the nation's character, curriculum and lesson plans, socialization. Implementation of character education through learning activities through extracurricular activities in the form of scouting, volleyball and through civilizing and habituation activities, namely exemplary, routine activities including Asmaul Husna, flag ceremonies and joint gymnastics and spontaneous activities. While in the evaluation using class assessment evaluation and evaluation meetings.